Directed evolution of a sequence-specific covalent protein tag for RNA labeling - Rongbing Huang; Alice Y. Ting (Proceedings of the National Academy of Sciences, 2025)
Efficient methods for conjugating proteins to RNA are needed for RNA delivery, imaging, editing, interactome mapping, and barcoding applications. Noncovalent coupling strategies using viral RNA binding proteins such as MS2/MCP have been widely applied but are limited by tag size, sensitivity, and dissociation over time. We took inspiration from a sequence-specific, covalent protein–DNA conjugation method based on the Rep nickase of a porcine circovirus called “HUH tag”. Though wild-type HUH protein has no detectable activity toward an RNA probe, we engineered an RNA-reactive variant, called “rHUH”, through 7 generations of yeast display–based directed evolution. Our 13.4 kD rHUH has 12 mutations relative to HUH and forms a covalent tyrosine-phosphate ester linkage with a 10-nucleotide RNA recognition sequence (“rRS”) within minutes. We engineered the sensitivity down to 1 nM of target RNA, shifted the metal ion requirement from Mn 2+ toward Mg 2+ , and demonstrated efficient labeling in mammalian cell lysate. This work paves the way toward a potentially powerful methodology for sequence-specific covalent protein–RNA conjugation in biological systems.